Aplicação da manutenção centrada em confiabilidade para um sistema de produção de vapor com caldeira biomassa - Pozzebon, Claiton Luiz (2017)
This paper deals with the application of the Reliability Centered Maintenance (MCC) program in the utility area of a biotechnology company in a biomass boiler steam production system. The search for increasing the reliability of systems and equipment is one of the main areas that has been receiving the attention of organizations. Increasingly, they are concerned with optimizing the use of available assets and assets, reducing risks associated with operational safety and the environment, and reducing operational costs. In this sense, the implementation of MCC represents a relevant contribution to the area of maintenance management. It presents in its stages several actions that in a structured way allow the definition of an adequate maintenance plan, which translates into gains to increase the reliability and availability of the assets of the company or organization. With this work of application of the MCC it was possible to identify several critical tasks that were not part of the maintenance plan and to organize the distribution of the tasks with those responsible for the execution. This study was very important to identify the critical parts that must be kept in stock and the technical resources necessary to perform the activities, and also allowed to identify some improvement opportunities to reduce the occurrence, or the severity of the failures, or to facilitate the detection of failures.